Atividades de inspeção no contexto de métodos ágeis - Toma, Karina Mitiko (2004)
Software inspection activities have became an important alternative to evaluate software artifacts in order to reach more quality in the development process. To support such activities, generally, reading techniques as OORTs/ProDeS are used, which is a set of techniques for the Object Oriented paradigm. These techniques are applied in a specific development process that uses UML notation, named ProDeS/UML. This process contemplates a gradual development, which facilitates artifacts evaluation as they are generated as well as its evolution. However, this process is directed to a traditional development, where information must be well documented that demands elaboration of different types of artifacts. Taking into account the most recent approach of Agile Methods, the first objective of this work was to evaluate the characteristics of these methods and to make the ProDeS/UML process more practical, in relation to the quantity of generated documentation. This task was realized based on the artifacts used by the main agile methods or other initiatives found in literature that use them jointly with other more traditional approaches. Once established the ProDeS/UML|pr process, the second objective was to verify which reading techniques of the OORTs/ProDeS set remained feasible to apply in this practical process and to elaborate laboratory packages that allow validating this set through experimental studies. Finally, the third objective, derived from the study of these methods, was to explore inspection activities for XP (Extreme Programming) that is considered in practice the most used agile method. An inspection strategy composed of a reading technique set that considers the requirements elicitation activities of XP was established. This strategy can be applied daily, with agility, according to the objectives of this method. Thus, the results of this work are the ProDeS/UML|pr process, the laboratory packages of the reading techniques that support inspection activities for this process and an inspection strategy for XP. In the scope of this work the laboratory package of one of the reading techniques for the ProDeS/UML|pr was evaluated through a feasibility study that was assessed by a group of students. According to this study the lab package seemed appropriate for controlled empirical studies